Family language policy, translingualism, and linguistic boundaries. Issue 2 (9th March 2020) - Jenks, Christopher
Abstract: The use of trans‐ constructs, such as trans‐languaging and translingualism, in current scholarship is party driven by a desire to create equitable learning opportunities for marginalized and minority students. While such efforts are important and must continue, it is also essential to explore the extent to which the theoretical principles emerging from trans‐language research are material for all individuals seeking to acquire multiple language resources. For example, do poststructuralist interpretations of linguistic boundaries, where individuals fluidly mix and move between language resources, provide an adequate lens through which to understand families seeking to maintain their heritage languages? This article addresses this question by reviewing past family language policy research. The review demonstrates that a one person – one language policy at home can be beneficial for some families, and that moving forward, trans‐language scholarship must thus resist the temptation to adopt a one‐size‐fits‐all approach to multilingualism.